(untitled) (Jurnal Bahasa, 2013)
Issues on greetings have been studied from the perspective of sociolinguistics and socio-pragmatics, mainly based on Politeness Theory and Speech Act Theory. However, there has to be a study conducted internationally or in Malaysia that enquires into greetings in terms of its logical form and propositional meanings. Looking at its logical form and anomalous propositional meanings, the usage of these greetings actually requires an indepth analysis. It has been claimed that propositional meaning of greetings are anomalous (some scholars claimed that greetings are zero semantically) and yet they are understood by hearers and widely used among speakers in daily communication. There must thus be a reason why greetings had survived over the years and this is reasonable grounds for analysis. Thus, by using the pragmatic approach mainly the Relevance theory, a research has been carried out to explain why logical forms of greetings as such are being used widely by native speakers of the Malay Language despite its propositional meaning being anomalous. Keywords: sociopragmatic, literal, anomaly, pragmatic, Relevance theory, relevance cognition and communication approach